Somatotype and dermatoglyphics in high income Brasilian volleyball, futsal, basketball and handball adult - Fernandes Filho, J.; Dantas, P. M. S.; Albergaria, M. B. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Dermathoglyphics is a genethical mark (1). In the sportive area studies it have been demonstrated that Delta index (D10) superior to 13,1 (big levels of coordination ) and the sum of total lines quantity (SQTL) superior to 136 ( increase of resistance) and the dimish of line number to the increase of strenght and potency levels (1) (4). The purpose of this study is centred in the somathotypical and dermathoglyphical profiles identification in high income of Brasilian male adult volleyball, footsal, basketball and handball and of adult female handball. Methods It is a Descriptive study whith an ex-post facto typoly. Volleyball Brasiliam Male Team/ 2000 n=22; National Male League/ 2001 n=66; Pan-American Male Basketball Team / 2003 n=12; Pan-American Female Handball / 2003, n=20. Dermathoglyphics Protocol(2) and somatotype, of Heath & Carter (3). Pattern-deviation Statistcs Media. The 196/96 article of human been in the experiments utilization. Discussion/Conclusions Volleyball and Futsal D10, predisposition and coordination, primordial to this kind of athlete; Futsal SQTL, predisposition to resistance and speed resistance; Volleyball and basketball, low resistance. Basketball D10, predisposition and coordination in a lower landing and for handball, the lower caractheristics for high income for coletive modalities. Digital prescriptions indicates: Volleyball - speed and movement potency; Futsal - resistance and speed resistance; Basketball - spedd resistance and potency and for handball - speed and movement potency. The strenght and stature somathotypes are for volleyball and basketball, footsal, adjusted to the modality of handball and high pecto- muscular It is suggested separated studies by group, according to the position and a correlative methodology can be utilizable for more elucidations and inferences to this and another modalities.